Reformulation of the Offence of Polygamy Without the Wife's Consent under Indonesia's 2023 Criminal Code: A Normative Legal Analysis - Pardomuan Putra Andespa Tambunan; Ivans Januardy; Satriya Nugraha; Andika Wijaya (CV. Era Digital Nusantara, 2026)
The Indonesian legal system establishes monogamy as the general principle of marriage while permitting limited exceptions through judicial authorization and the wife's consent under the Marriage Law. The enactment of the 2023 Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) reformulates the offence of unauthorized polygamy, creating new legal challenges concerning criminalization, legal certainty, and the relationship between criminal law and family law. Previous studies have predominantly examined polygamy from family law, Islamic law, or criminal law perspectives in isolation, leaving limited analysis of the criminalization rationale, comparative legal policy, and normative harmonization between the 2023 Criminal Code and the Marriage Law. This study aims to analyze the normative construction of the offence of polygamy without the wife's consent, evaluate its criminal law policy rationale, and develop an ideal framework for its reformulation within Indonesia's national legal system. This study employs normative juridical research using statutory, conceptual, case, and comparative approaches. Primary legal materials comprise the 2023 Indonesian Criminal Code, the Marriage Law, constitutional jurisprudence, judicial decisions, and relevant legal doctrines, which are analyzed through qualitative prescriptive methods using grammatical, systematic, and teleological interpretation. The findings reveal that the reformulated offence reflects a shift in criminal law policy from protecting the formal legality of marriage toward safeguarding women's rights and family integrity. However, three principal weaknesses remain: the ambiguous legal meaning of the wife's consent, the absence of clear boundaries between administrative violations and criminal offences, and normative disharmony between the Criminal Code and the Marriage Law, creating the potential for inconsistent law enforcement and overcriminalization. This study contributes theoretically by developing a rights-based criminalization framework grounded in proportionality, legal certainty, and human rights protection, while proposing a conceptual model integrating criminal law and family law to guide future harmonization of the 2023 Indonesian Criminal Code and the Marriage Law.